An Uncomfortable Fit: Fatness, Femininity and the University - Gullage, Amy (Atlantis, 2010)
Drawing on interviews conducted with self-identified fat women undergraduates, this paper examines how universities construct and reproduce dominant understandings of fatness. Specifically, three inter-related discursive practices are discussed: manoeuvring physical space on campus, constructing subversive subject-positions and confronting the silence and denial of fatness.